The Rice Eukaryotic Translation Initiation Factor 3 Subunit f (OseIF3f) Is Involved in Microgametogenesis - Li, Qi; Deng, Zhuyun; Gong, Chunyan; Wang, Tai (Frontiers in Plant Science, 2016)
Microgametogenesis is the postmeiotic pollen developmental phase when unicellular microspores develop into mature tricellular pollen. In rice, microgametogenesis can influence grain yields to a great degree because pollen abortion occurs more easily during microgametogenesis than during other stages of pollen development. However, our knowledge of the genes involved in microgametogenesis in rice remains limited. Due to the dependence of pollen development on the regulatory mechanisms of protein expression, we identified the encoding gene of the eukaryotic translation initiation factor 3, subunit f in Oryza sativa (OseIF3f). Immunoprecipitation combined with mass spectrometry confirmed that OseIF3f was a subunit of rice eIF3, which consisted of at least 12 subunits including eIF3a, eIF3b, eIF3c, eIF3d, eIF3e, eIF3f, eIF3g, eIF3h, eIF3i, eIF3k, eIF3l and eIF3m. OseIF3f showed high mRNA levels in immature florets and is highly abundant in developing anthers. Subcellular localization analysis showed that OseIF3f was localized to the cytosol and the endoplasmic reticulum in rice root cells. We further analyzed the biological function of OseIF3f using the double-stranded RNA-mediated interference (RNAi) approach. The OseIF3f-RNAi lines grew normally at the vegetative stage but displayed a large reduction in seed production and pollen viability, which is associated with the down-regulation of OseIF3f. Further cytological observations of pollen development revealed that the OseIF3f-RNAi lines showed no obvious abnormalities at the male meiotic stage and the unicellular microspore stage. However, compared to the wild type, OseIF3f-RNAi lines contained a higher percentage of arrested unicellular pollen at the bicellular stage and a higher percentage of arrested unicellular and bicellular pollen, and aborted pollen at the tricellular stage. These results indicate that OseIF3f plays a role in microgametogenesis.